Impact of Ethnicity on COVID-19 Related Hospitalizations in Children During the First Pandemic Wave in Northern Italy - Baronio, Roberto; Savaré, Lucia; Ruggiero, Jessica; Crotti, Beatrice; Mazza, Angelo; Marseglia, Gian Luigi; Dodi, Icilio; Cavalli, Claudio; Schumacher, Richard Fabian (Frontiers in Pediatrics, 2021)
There is increasing evidence that black people and other minorities have a higher incidence of severe COVID-19 disease, but little is known about the situation of children, especially in Europe. In general children are less infected and if so, frequently show mild or asymptomatic disease, making conclusions difficult. We collected data on SARS-CoV-2 associated hospitalizations in a well-defined population of 550,180 children up to 15 years in five hub-centers during the “first wave” at the heart of the pandemic in Northern Italy. Among the 451,053 Italian citizens 80 were hospitalized as compared to 31 out of 99,127 foreign citizens, giving a significantly higher risk (odds ratio 1.76; 95% CI: 1.16 – 2.66) for the foreign children. The risk was highest for children of African ethnicity as compared to Italians with an odds ratio of 2.76 (95% CI: 1.56 – 4.87). None of the patients deceased. There was no significant difference in age (thou infants regardless of ethnicity had a ten-fold higher risk), sex, length of hospitalization or comorbidities, namely overweight. As bureaucratic, cultural and information barriers mostly affect preventive and adult services and considering that in contrast to other countries, in Italy pediatric care is guaranteed free of (out-of-pocket) charge to all people less than 16 years, and hospitals are densely spaced, access to health care seems to be a minor problem.Thus other possible root causes are discussed. We believe that this is an unbiased starting point to understand and overcome the reasons for the higher risk those children experience.